VD_FINDINFO Réc-civile / 2019 / 24 vom 30. Juli 2019 - VD Tribunal cantonal (2019)
RÉCUSATION, REJET DE LA DEMANDE, JUGE DE PAIX | 47 al. 1 let. a CPC (CH), 47 al. 1 let. f CPC (CH), 49 al. 1 CPC (CH), 8a al. 1 CDPJ, 8a al. 3 CDPJ